Prediction of the structural and electronic properties of MoxTi1−xS2 monolayers via first principle simulations. (20th October 2020) - Verma, Ankit Kumar; Raffone, Federico; Cicero, Giancarlo
Two-dimensional transition metal dichalcogenides have gained great attention because of their peculiar physical properties that make them interesting for a wide range of applications. Lately, alloying between different transition metal dichalcogenides has been proposed as an approach to control two-dimensional phase stability and to obtain compounds with tailored characteristics. In this theoretical study, we predict the phase diagram and the electronic properties of Mo x Ti1− x S2 at varying stoichiometry and show how the material is metallic, when titanium is the predominant species, while it behaves as a p -doped semiconductor, when approaching pure MoS2 composition. Correspondingly, the thermodynamically most stable phase switches from the tetragonal to the hexagonal one. Further, we present an example which shows how the proposed alloys can be used to obtain new vertical two-dimensional heterostructures achieving effective electron/hole separation.